2021
DOI: 10.3390/ijms22116123
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Approach to Identify Quantitative Trait Loci for Drought Tolerance in Tetraploid Potato (Solanum tuberosum L.)

Abstract: Drought represents a major abiotic stress factor negatively affecting growth, yield and tuber quality of potatoes. Quantitative trait locus (QTL) analyses were performed in cultivated potatoes for drought tolerance index DRYM (deviation of relative starch yield from the experimental median), tuber starch content, tuber starch yield, tuber fresh weight, selected transcripts and metabolites under control and drought stress conditions. Eight genomic regions of major interest for drought tolerance were identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 104 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…QTL detection of hollow heart is affected by the environment [ 27 ] and genetic background [ 27 , 62 ], since both have effects on the expression of a trait which is the result of the genes responsible. Potential candidate genes in the vicinity of SNP peaks for hollow heart associated with heat and drought stress in potatoes include, Ubiquitin-protein ligase [ 52 , 63 ], Laccase [ 64 ], BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase [ 65 ], Mads box protein [ 63 ], and Zinc finger protein [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…QTL detection of hollow heart is affected by the environment [ 27 ] and genetic background [ 27 , 62 ], since both have effects on the expression of a trait which is the result of the genes responsible. Potential candidate genes in the vicinity of SNP peaks for hollow heart associated with heat and drought stress in potatoes include, Ubiquitin-protein ligase [ 52 , 63 ], Laccase [ 64 ], BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase [ 65 ], Mads box protein [ 63 ], and Zinc finger protein [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here are significant because they derive from a unique and unprecedented mutagenized diploid germplasm panel. All previous mapping studies for the drought-tolerance trait have focused on bi-parental populations ( Anithakumari et al, 2012 ; Khan et al, 2015 ; Schumacher et al, 2021 ); to our knowledge, no previous investigations have reported GWAS mapping for maturity and drought traits in diploid potatoes. Moreover, in the context of changing climate, the identification and development of early-maturity potatoes and potatoes that are drought tolerant are sought as a climate adaptation solution for short- and long-season growing areas.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the genes were identified in a close vicinity (0.5–1 kb) of the QTNs, suggesting their true impact on the traits. In their study using an indirect yield trait (DRYM) for drought tolerance in tetraploid potatoes, Schumacher et al (2021) reported candidate genes for drought tolerance, albeit from very large (1.3 Mb–36.76 Mb) genomic regions. Our data are, thus, highly relevant for targeted gene studies and marker development when compared with the report by Schumacher et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most plants depend on the root system to supply the water and minerals essential for the growth and maintenance of the aboveground organs. A balance is established between the development of the branches and leaves and the development of the root system [ 31 , 32 ]. The development of the root system is much greater than that of the aboveground parts, and the total area of the root system in contact with the soil often exceeds the area of the stem and leaves by a factor of 6–16 [ 33 ].…”
Section: Current Status Of Research On Genes Associated With Root Gro...mentioning
confidence: 99%